Biochar improved the composting quality of seaweeds and cow manure mixture and altered the microbial community - Jia, Haijiang; Chu, Depeng; You, Xiangwei; Li, Yiqiang; Huang, Chongjun; Zhang, Jili; Zeng, Xiangnan; Yao, Hui; Zhou, Zhaofeng (Frontiers in Microbiology, 2022)
The beneficial effects of biochar addition during composting have been proved for many feedstocks, like manures and crop straws. However, the effect of biochar on the quality of composting product with seaweed as the feedstock and the bacterial response has not been investigated. In this study, the wheat straw biochar addition on the quality of the composting product and the bacterial response was explored at the rate of 0-10%. The results showed that biochar addition at the optimal rate (5%, w/w) could increase the germination index (GI) and the ratio of the optical density of humic acid at 460 nm to that at 660 nm (E4/E6) of the composting product, which indicated the decreased biotoxicity and enhanced compost maturity. The significant increase of the ammonium nitrogen (NO3--N) content of the composting product proved the improvement of N cycling during composting process with biochar addition. The bacterial community of composting product was shifted and the relative abundance of some beneficial taxa (e.g. Muricauda and Woeseia) were significantly increased with biochar addition. Furthermore, the relative abundance of some bacterial genes related to amino acid metabolism and carbohydrate metabolism were also increased with biochar addition. The results of our study provided the positive effect of biochar addition on the composting of seaweed and could help to produce high quality seaweed fertilizer by composting with biochar addition.